The Role of Sharia Management in Promoting Corporate Sustainability in the Digital Economy Era - Yansen, Albert; Herawati, Ermi; Miri, Usman H (International Journal of Sharia Business Management, 2024)
This study aims to explore the role of sharia management in improving corporate sustainability in the digital economy era. This study focuses on how sharia principles can be applied in management strategies to achieve long-term sustainability in an increasingly connected and digital context. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with managers and sharia management practitioners in various companies that have implemented sharia principles. The results of this study indicate that the implementation of sharia management can make a significant contribution to corporate sustainability in the digital era. Sharia principles, such as fairness, transparency, and social responsibility, have been shown to improve corporate reputation, strengthen relationships with stakeholders, and optimize operational efficiency. This study concludes that sharia management plays an important role in improving corporate sustainability in the digital economy era. The implementation of sharia principles not only helps companies fulfill their social and ethical responsibilities, but also contributes to the efficiency and competitiveness of the company